Who owns the moon? : and other conundrums of exploring and using space - Levinson, Cynthia; Swanson, Jennifer (Margaret Quinlin Books, Peachtree, 2025)
"Are you ready for your first trip to the Moon? Today's teens may travel to multiple planets and moons in their lifetimes. This book is a primer on what to know for a future in space. It combines technology and science with law and policy for a fascinating look at a very timely subject"--